“微电影”与“大电影”的承继与反哺 ——从“11 度青春”《老男孩》到《老男孩之猛龙过江》 The inheritage and return nurturing between the Microfilm and the Big Movie ——from the“11 Degrees of Youth“,“Old Boy“ to the “Old Boys：The Way of The Dragon“ - Meng Shuguang; Xue Mei (Journal of Language, Literature and Teaching, 2019)
在互联网时代的“微革命”浪潮中，电影家族也迎来了新成员——“微电影”。那么，“微电影”与传统的“大电影”之间到底是各行其道， 还是相得益彰、并驾齐驱呢？笔者以“微电影” ——“11 度青春”《老男孩》与“大电影”——《老男孩之猛龙过江》及其之间的承继与反哺关系为例对这一问题进行探讨。“大电影”《老男孩之猛龙过江》无论在观众基础、题材音乐，还是在导演演员等方面，都极大程度地承继了“微电影”《老男孩》的成功因素，“微电影”为“大电影”奠基铺路。另一方面，“微电影”《老男孩》在营销传播、宣传互动，以及为“大电影”培养新生力量、储备后备人才方面体现出对“大电影”《老男孩之猛龙过江》的补充与反哺。因此，微时代下“微电影”的欣欣向荣并不是对传统“大电影”的取而代之，而是与之承继反哺、相得益彰、并驾齐驱、良性互动、共同发展的。我们希望，“微电影”与“大电影”之间能够形成更好的良性互动关系，希望更多的“微电影”能像《老男孩》一样，最终走进影院，延伸“大电影”的产业链。In the tide of micro-revolution in the internet era, the film family has alsoushered in a new membe“r  Micro-Film”. So, is micro-film different from the traditional“Big Film”or do they complement each other and keep pace with each other? The author takes“Micro- Film”——“11 Degrees of Youth”,“Old Boy”and“Big Film”——“Old Boys：The Way of The Dragon” and its relationship of inheritance and return nurturing as an example to discuss this issue. “ Big Film”,“Old Boys：The Way of The Dragon”,have inherited to a great extent the success factors of “ Micro-Film ” , “ Old Boy ” , in terms of audiences, theme music, directors and actors, and “ Micro-Film” paves the way for “ Big Film”. On the other hand, “ Micro-Film”, “ Old Boy”,complement and return nurture to“Big Film”, “Old Boys：The Way of The Dragon”, in marketing, communication, publicity and interaction, as well as in training new forces and reserving Supportive talents for “Big Film”. Therefore, the flourishing of “Micro-Film” in the micro-era is not to replace the traditional “Big Film”, but to inherit and return nurturing, complement each other, keep pace with each other, interact benignly and develop together with it. We hope that there will be a better interaction between “Micro Film” and “Big Film”, and more “Micro Film” like “Old Boy”will eventually enter the cinema and extend the industry chain of “Big Film”.